Compositional Grading in Oil and Gas Reservoirs - Oliveira Esposito, Rogerio; Rodrigues Alijó, Pedro Henrique; Scilipoti, Jose Antonio; Wanderley Tavares, Frederico (Elsevier Science & Technology, 2017)
This title offers instruction, examples, and case studies on how to answer the challenges of modeling a compositional gradient subject. Starting with the basics on PVT analysis, applied thermodynamics, and full derivations of irreversible thermodynamic-based equations, this critical reference explains gravity-modified equations to be applied to reservoirs, enabling engineers to obtain fluid composition at any point of the reservoir from measured data to create a stronger model calibration.